Distribution of multimedia data over a wireless network: An introduction / Rafidah Md. Noor - Md. Noor, Rafidah (2004)
This paper presents the introduction of the distribution multimedia data over a wireless network. Providing quality of service (QoS) guarantees is an important requirement for multimedia data in wireless environment. Most components of multimedia such as word processor files, graphics, and images require data or file transfer, sometimes isochronous with audio or video information that means data should arrive in time. There are several issues that must be addressed when investigating multimedia data delivery; hardware, network, network design, software and protocol issues. These applications are time-critical and may have many different QoS requirements. The paper concludes with a brief view of related issues in wireless environment.